The role of modern agricultural technologies in improving agricultural productivity and land use efficiency - Chen, Xie (Frontiers in Plant Science, 2025)
Modern agricultural technologies are crucial for addressing global food security and environmental sustainability challenges amidst a growing population and climate change. These innovations, including precision agriculture, biotechnology, smart irrigation, automation, vertical farming, and artificial intelligence (AI), significantly enhance productivity and land use efficiency. Precision agriculture, utilizing GPS, drones, and IoT, improves yields by 20–30% and cuts input waste by 40–60%. Biotechnology, with CRISPR and GMOs, delivers drought and pest-resistant crops, stabilizing yields, as seen with Bt cotton reducing pesticide use by 50% in India. Smart irrigation boosts water efficiency by 40–60%, while automation and robotics mitigate labor shortages and reduce costs by 25%. Vertical farming increases yields 10–20 times with 95% less land and water, supporting urban food security. AI analytics enhance decision-making with over 90% accuracy in forecasting and resource allocation. Despite these benefits, high costs, technological illiteracy, and regulatory issues hinder adoption, especially among smallholders. Policy support, public-private partnerships, and training are vital for broader technology access and fair benefits. Integrating renewable energy and circular economy principles into aggrotech presents a path to sustainability. This review highlights the transformative potential of modern technologies for sustainable intensification, increasing productivity without expanding farmland, while lessening environmental impacts. It underscores the need for coordinated efforts to overcome adoption challenges and harness these innovations for global food security and climate resilience.